MODERN PROBLEMS OF SPIRITUAL EDUCATION IN UKRAINE: THE QUESTION OF THE STATUS OF THEOLOGY - Tatiana Levchenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article shows a significant similarity of the claims of philosophy and theology to the status of meta-science and universal philosophical discourse. Historically, these claims relate to the doctrine of a special intuitive cognition, but today they are manifested in an attempt to answer the main ideological questions of the individual. It is proved that the claims of theology to the status of metascience are less substantiated than in philosophy, since theology cannot provide methodology for specific sciences, cannot, without the mediation of philosophy, evaluate scientific theories. Also, the theologian is not free in his own reflections, even if he exhibits creative spontaneity, because it must necessarily be rooted in a certain tradition. Utopian are the hopes of Catholic, Orthodox and Protestant theologians that theology with the end of the modern era can again qualify for the status of meta-science and evaluate the achievements of all sciences, especially humanitarian ones.